2020
DOI: 10.3390/jcm9093059
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Psychological Distress and Sleep Quality on Balance Confidence, Muscle Strength, and Functional Balance in Community-Dwelling Middle-Aged and Older People

Abstract: The objective was to evaluate the associations of psychological distress and sleep quality with balance confidence, muscle strength, and functional balance among community-dwelling middle-aged and older people. An analytical cross-sectional study was conducted (n = 304). Balance confidence (Activities-specific Balance Confidence scale, ABC), muscle strength (hand grip dynamometer), and functional balance (Timed Up-and-Go test) were assessed. Psychological distress and sleep quality were evaluated by the Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…In another study, where Fabrega-Cuadros et al [32] assessed the impact of psychological distress and sleep quality on balance confidence, muscle strength, and functional balance in 304 community-dwelling middle-aged and older adults, the results of their multivariate linear and logistic regressions showed higher anxiety values, fatigue, and using sleep medication were linked to falling. Anxious older adults were also found to exhibit less proficiency on standing at an elevated level and undergoing postural sway tests than non anxious control subjects [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, where Fabrega-Cuadros et al [32] assessed the impact of psychological distress and sleep quality on balance confidence, muscle strength, and functional balance in 304 community-dwelling middle-aged and older adults, the results of their multivariate linear and logistic regressions showed higher anxiety values, fatigue, and using sleep medication were linked to falling. Anxious older adults were also found to exhibit less proficiency on standing at an elevated level and undergoing postural sway tests than non anxious control subjects [33].…”
Section: Resultsmentioning
confidence: 99%
“…Elderly fallers/near fallers may develop post fall anxiety Downton et al [47] Older fallers have higher anxiety rates than non fallers Fabrega-Cuadros et al [32] Greater anxiety and sleep medication heighten falls risk Hallford et al [29] There is a link between anxiety and falling Holloway et al [30] There is an association between falling and anxiety in men anxiety, and with this falls vulnerability among older possibly immunocompromised and chronically ill community living adults [50] that warrants immediate and carefully considered public health interventions 24]. Indeed, without immediate and dedicated efforts, it is likely that persistent falls injuries, including more severe injuries than those presently being reported since the inception of the pandemic, will ensue, even though many other forms of injurious trauma have been found to decline.…”
Section: Ang Et Al [24]mentioning
confidence: 99%
“…Rivasi et al, in a study with a sample of community-dwelling people aged ≥60 years, found that, among others, participants who were older at baseline and had higher levels of depression and anxiety developed a fear of falling in a two-year follow up, although only the first two factors remained in the multivariate analysis [ 47 ]. Finally, sleep problems and greater levels of self-perceived fatigue have been associated with decreased balance confidence and greater fall risk in community-dwelling older adults [ 48 , 49 ]. This is in accordance with our findings, in which a high risk of falling assessed by the ABC-16 was related to anxiety and shorter sleep duration, as well as with SARC-F scores.…”
Section: Discussionmentioning
confidence: 99%
“…2020 m. Ispanijoje buvo atliktas tyrimas, siekiant įvertinti bendruomenėje gyvenančių vidutinio ir vyresnio amžiaus žmonių psichologinio distreso ir miego kokybės sąsajas su raumenų jėga ir funkcine pusiausvyra (pusiausvyros išlaikymas). Šio tyrimo rezultatai parodė, kad didesnis nerimo lygis ir vaistų nuo miego sutrikimų vartojimas buvo susiję su kritimų rizika ir atitinkamai prastesne funkcine pusiausvyra [16].…”
Section: Vidutinio Amžiaus Ir Pagyvenusių žMonių Miego Kokybėunclassified